Instrumentos líticos para a deformação plástica de metais do povoado calcolítico de Outeiro Redondo (Sesimbra) - Cardoso, João Luís (2018)
Excavations undertaken at the fortified Chalcolithic settlement of Outeiro Redondo between 2005 and 2016 produced an assemblage of eight stone implements likely used in the plastic deformation of metals. All implements come from clearly defined contexts of the Middle / Late Chalcolithic, within a sector of the site that has also produced copious other evidence for metallurgical activities. Drawing on archaeological and ethnografic comparisons, we discuss the choice of raw material and the morphology of these implements in terms of their manufacture, as well as their role in the operational sequence of Chalcolithic metalwork prodution. We also consider their potencial to inform inferences concerning the social division of labour in Chalcolithic society.